A multiphase first order model for non-equilibrium sand erosion, transport and sedimentation. (July 2015) - Preziosi, L.; Fransos, D.; Bruno, L.
Abstract: Three phenomena are involved in sand movement: erosion, wind transport, and sedimentation. This paper presents a comprehensive easy-to-use multiphase model that include all three aspects with a particular attention to situations in which erosion due to wind shear and sedimentation due to gravity are not in equilibrium. The interest is related to the fact that these are the situations leading to a change of profile of the sand bed.